Etnografia widzialności: zdjęcia jako informatorzy - Rapior , Waldemar (Człowiek i Społeczeństwo, 2013)
Ethnography requires immersion in the field work and the adoption of two perspectives: internal and external. Pure visibility, says Lambert Wiesing, presents things as exclusively visible, released from the laws of physics. You can touch material objects – that entails the possibility of hearing, smelling, and vision. Images could be printed: we feel the smell of ink and a printing machine, texture of media – paper, cardboard or foil. However Wiesing stresses: all we experience in a picture are the qualities detectable by the sense of sight. In this article I present the arguments that the images may be the informants, and ethnography of visibility allows us for awakening the sociological imagination and for analyzing material and visual aspect of the practices. Arguments are based on the interviews conducted with the “Invisible city” project team as well as on the analysis of images from the database: www.niewidzialnemiasto.pl.